Pro-oxidant/antioxidant balance during a prolonged exposure to moderate altitude in athletes exhibiting exercise-induced hypoxemia at sea-level - Raberin, A.; Nader, E.; Ayerbe, J. L.; Alfonsi, G.; Mucci, P.; Rytz, C. L.; Pialoux, V.; Durand, F. (Life, 2021)
This study examined to what extent athletes exhibiting exercise-induced hypoxemia (EIH) possess an altered redox status at rest, in response to exercise at sea level (SL) and during moderate altitude exposure. EIH was defined as a fall in arterial O2 saturation of at least 4% during exercise. Nine endurance athletes with EIH and ten without (NEIH) performed a maximal incremental test under three conditions: SL, one (H1) and five (H2) days after arrival to 2400 m. Gas exchange and peripheral capillary oxygen saturation (SpO2) were continuously monitored. Blood was sampled before exercise and after exercise cessation. Advanced oxidation protein products (AOPP), catalase, ferric-reducing antioxidant power, glutathione peroxidase, superoxide dismutase (SOD) and nitric oxide metabolites (NOx) were measured in plasma by spectrophotometry. EIH athletes had higher AOPP and NOx concentrations at pre- and post-exercise stages compared to NEIH at SL, H2 but not at H1. Only the EIH group experienced increased SOD activity between pre- and post-exercise exercise at SL and H2 but not at H1. EIH athletes had exacerbated oxidative stress compared to the NEIH athletes at SL and H2. These differences were blunted at H1. Oxidative stress did not alter the EIH groups` aerobic performance and could lead to higher minute ventilation at H2. These results suggest that higher oxidative stress response EIH athletes could be involved in improved aerobic muscle functionality and a greater ventilatory acclimatization during prolonged hypoxia.